10х²+19х-2=10(х-0,1)(х+2)
Есть формула:
![ax^2+bx+c=a(x-x_1)(x-x_2) ax^2+bx+c=a(x-x_1)(x-x_2)](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3Da%28x-x_1%29%28x-x_2%29)
Найдем корни:
10х²+19х-2=0
d=b^2-4ac=361-4*10*(-2)=441 √441=21
x1=-2, x2=0,1
Подставим в формулу:
![a(x-x_1)(x-x_2)=10(x-0,1)(x-(-2))=10(x-0,1)(x+2) a(x-x_1)(x-x_2)=10(x-0,1)(x-(-2))=10(x-0,1)(x+2)](https://tex.z-dn.net/?f=a%28x-x_1%29%28x-x_2%29%3D10%28x-0%2C1%29%28x-%28-2%29%29%3D10%28x-0%2C1%29%28x%2B2%29)
0,5х²-5,5х+15=0,5(х-6)(х-5)
Найдем корни:
d=b^2-4ac=30,25-4*0,5*15=0,25 √0,25=0,5
x1=5, x2=6
Подставим в формулу:
![a(x-x_1)(x-x_2)=0,5(x-(-5,5)(x-15)= a(x-x_1)(x-x_2)=0,5(x-(-5,5)(x-15)=](https://tex.z-dn.net/?f=a%28x-x_1%29%28x-x_2%29%3D0%2C5%28x-%28-5%2C5%29%28x-15%29%3D)